THE EFFECT OF WORK-LIFE BALANCE, WORK STRESS AND WORK MOTIVATION ON JOB SATISFACTION THROUGH PSYCHOLOGICAL CAPITAL ON BNN MILLENIAL EMPLOYEES IN RIAU ISLANDS - Amelia Widya Saputri, Meta; Khaddafi, Muammar; Catrayasa, I Wayan; Indrayani, Indrayani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine and examine the effect of work-life balance, work stress and work motivation on employee job satisfaction with psychological capital as an intervening variable. The method used in this study uses a quantitative approach, data collection using a questionnaire and distributed to 81 respondents. Statistical data analysis using SEM-PLS (Structural Equation Modeling-Partial Least Square) and using path analysis to examine the pattern of relationships that reveal the influence of variables with other variables. Both direct and indirect effects use the Smart PLS Ver 3.0 software. The results showed that the work-life balance directly had a positive and significant effect on psychological capital with a p-value of 0.004 <0.05,